The narrative proportion in Surat Al Baqarah Study in the guidance of the appropriate science - Alaobaidy, Zahraa K.; ALtobchy, Talal E. (Humanities Journal of University of Zakho, 2013)
Proportionality is considered as one of the most important signs of Quranic interpretation. It is a study of the miracles of the Qur'an and the characteristics of its style. The Quran's miracles lie in showing the integration of the Quranic systems in the single surah through the suitability of its stories and the unity of it within the science of Sharif which is the science of proportional. This research aims to highlight the unity of Al-Baqarah - a model of the Holy Qur'an - and to show the special systems of this sura in terms of arranging their stories to reveal the reasons for choosing methods of systems in order and consistency. Linking it to its subjects, contents and purposes. And from the adoption of the thematic links between the stories of Surat al-Baqarah and what was announced by proof of the stories of the various purposes and objectives all pour into the subject of Sura, which is what the research sought to show its objectives within one objective unit, Contexts.